2020
DOI: 10.1177/0190272520976133
|View full text |Cite
|
Sign up to set email alerts
|

Managing “Stable” Cancer News

Abstract: This study focuses on oncology interviews with returning patients who have been diagnosed with cancer, are undergoing various treatment regimens, and have been informed by doctors of their current “stable” medical condition. Conversation analysis was conducted on 112 video recorded and transcribed oncology interviews involving 30 doctors. In 44 of 112 (39 percent) interviews, doctors announced stable as good cancer news. In response, patients rarely affirm stable as good news for them. Nonreponses and minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Patient is aware, and oncologist confirms, that her condition is likely not curable and many prognostic uncertainties remain. An explicit and shared clinical goal stated in this interview, however, is to control her cancer as a stable but chronic health threat, with interventions designed to minimize dangerous metastasis while maintaining a reasonably high quality of living (Beach, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient is aware, and oncologist confirms, that her condition is likely not curable and many prognostic uncertainties remain. An explicit and shared clinical goal stated in this interview, however, is to control her cancer as a stable but chronic health threat, with interventions designed to minimize dangerous metastasis while maintaining a reasonably high quality of living (Beach, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Addressing the complexities of patients' emotional and psychosocial concerns remains an ongoing challenge across a wide variety of clinical environments . Patient-initiated actions are frequently met with providers' avoidance and resistance, actions such as answering more than a doctor's question asked by providing extended illness stories (Stivers & Heritage, 2001), justifying wellness (Beach, 2013b), challenging and resisting doctors' authority to impose order on patients' lives (Beach, 2021;Stivers & Timmermans, 2020), or attempts to recruit doctors' support by invoking hopeful outcomes (Beach, 2014). The findings from this case study identify alternative, compassionate caring practices for sharing and attempting to assuage patients' suffering.…”
mentioning
confidence: 99%
“…In addition, previous research has shown that patients and clinicians hold different perspectives and priorities concerning 2/22 disease [14,64]. For example, patients usually consider news of a 'stable' cancer as being negative, while doctors often consider this to be positive [9]. Meanwhile, analysis of an online Uveitis patient forum identified different language and priorities than those expressed by existing scientific and clinical knowledge resources [50].…”
Section: Introductionmentioning
confidence: 99%